Inteligencia emocional y agresividad en aspirantes del centro de nivelación Académica ¨Pucará¨, Riobamba, 2020 - Johanna Marcela, Moreno Ayala (2021)
ABSTRACT: The research's main objective was to analyze emotional intelligence and aggressiveness, and the population was made up of 50 applicants from the Centro de Nivelación Académica "PUCARÁ." The methodology is based on a quantitative approach using psychometric tests: Trait-Meta Mood Scale and the AQ Aggressiveness Questionnaire. Among the main results with the EI: 41% of men and 61% of women correspond to an adequate level of care; 47% of men and 61% of women have an adequate level of clarity, and 44% of men and 67% of women present an adequate level of reparation. About aggression, it was determined that within physical aggression, 44% of men have a medium level and 50% of women a deficient level; in the verbal aggression subscale, 41% of men have a very high level and 33% of women a medium level of aggression; in the anger subscale, 41% of men have a very high level and 39% of women a deficient level; in the hostility subscale, 44% of men have a medium level and 50% of women a high level. Within the aggressiveness, 44% of men present high aggressiveness, and 33% of women have low aggressiveness. Due to the results, a proposal for psychological intervention has been developed to train Emotional Intelligence and reduce the applicants' levels of aggression.